Pharmacoepidemiology of metaraminol in critically ill patients with shock in a tertiary care hospital. Issue 6 (November 2021) - Sardaneh, Arwa Abu; Penm, Jonathan; Oliver, Matthew; Gattas, David; McLachlan, Andrew J.; Patanwala, Asad E.
Abstract: Background: Metaraminol is increasingly used as a vasopressor in critically ill patients. Nevertheless, there remains limited evidence to support its use in international guidelines for management of shock. Objectives: The aim of the study was to describe the pharmacoepidemiology of metaraminol in critically ill patients with shock. Methods: A retrospective observational study was conducted in an intensive care unit (ICU) in Sydney, Australia. Patients admitted during a 1-year time frame who received metaraminol intravenous infusions for management of shock were included. Results: A total of 152 patients were included. When metaraminol was used, it was the most common first-line vasopressor started for management of shock (97%, n = 147) and was used as monotherapy in 53% (n = 81) of patients. The median duration of metaraminol infusion in the ICU was 7 h (interquartile range [IQR] = 3 to 19), and the median maximum metaraminol infusion rate in the ICU was 4.0 mg/h (IQR = 2.5 to 6.0). Peripheral vasopressor infusions were used in 96% (n = 146/152) of patients for a median duration of 7 h (IQR = 2 to 18). In all these cases, the peripheral vasopressor used was metaraminol (100%, n = 146/146). Patients were commonly switched from metaraminol to noradrenaline infusions after insertion of a central venous catheter (R2 = 0.89). Patients treated with metaraminol monotherapy had a lower Acute Physiology and Chronic Health Evaluation III score (58 vs 68; median difference = −9, 95% confidence interval = −16 to −3; p < 0.01) and a shorter duration of overall vasopressor use in the ICU (12 vs 39 h, median difference = −24 h, 95% confidence interval = −31 to −18; p < 0.01) than those treated with combination vasopressors. No extravasation injury was reported in the study cohort. Conclusions: Metaraminol is often administered as a first-line peripheral vasopressor in the ICU and is used as a single agent in patients with lower severity of shock.